(3-Aminopropyl)trimethoxysilane Self-Assembled Monolayer as Barrier of Porous SiOCH for Electroless Cu Metallization: Optimizations of SiOCH Hydroxylation and Monolayer Functionalization. (5th February 2021) - Fang, Jau-Shiung; Yang, Tzu-Ming; Cheng, Yi-Lung; Chen, Giin-Shan
Abstract : Self-assembled monolayers (SAMs) are potential diffusion barriers of nanoporous carbon-doped organosilica (p-SiOCH) for Cu metallization. A concern regarding silanization of the p-SiOCH using a wet chemical process is that its dielectric properties and bonding structures could be damaged by the chemical solution used, which is rarely addressed. In this study, the capacity of various (3-aminopropyl)trimethoxysilane self-assembled monolayers (APTMS-SAMs) as a barrier of p-SiOCH for electroless Cu metallization is evaluated. The processing of hydroxylation of the p-SiOCH (for silanization) and functionalization of APTMS-SAMs (for seeding of electroless metallization) was controlled through examining dielectric properties and bond structures of the hydroxylated p-SiOCH and functionalized APTMS-SAMs. Through tailoring the wet chemical treatments, the dielectric constant, insulating capacity, and bonding structure of post-treated p-SiOCH could be preserved at the pristine states, and the APTMS-SAM fabricated turns out to be a reliable barrier thermally stable up to 500 °C, 100 °C greater than that of the p-SiOCH without an SAM barrier. The integration of electroless Cu metallization reliably with p-SiOCH using a near-zero-thickness monolayer (free of a conventional metallic barrier) in an all-wet manner will be demonstrated. However, to make this approach working, both the hydroxylation of p-SiOCH and functionalization of APTMS-SAM have to be optimized.